Imagining the future: central axes for a University Social Responsibility model - González Rodríguez, Guillermo Isaac (Emerging Trends in Education, 2022)
The university mission is a subject of debate that has been considered for some decades, as something that must be reformed to meet the needs of different contexts. This paper makes an approach to the role that universities assume with respect to their mission and their substantive functions in order to assimilate social problems and thus respond to the Sustainable Development Goals (SDG). The objective is to describe the main elements that are found around a model of USR in order to face the postmodern stage. For this, the 2030 agenda of the United Nations (UN) is taken as the central axis, as well as the positions of social knowledge management and the USR for the analysis. As results, a series of elements are offered that can serve as the basis for the formulation of a Model of social use of knowledge through the development of projects from the university that are applicable to the social environment and with which it is promoted in the academic community and student, an awareness of the problems that must be addressed as a priority according in the different social spheres. Keywords: Mission; University Social Responsibility; Sustainable development goals; Social management of knowledge; University.